2011
DOI: 10.1523/jneurosci.3667-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

CX3CR1 Deficiency Leads to Impairment of Hippocampal Cognitive Function and Synaptic Plasticity

Abstract: The protective/neurotoxic role of fractalkine (CX3CL1) and its receptor CX3C chemokine receptor 1 (CX3CR1) signaling in neurodegenerative disease is an intricate and highly debated research topic and it is becoming even more complicated as new studies reveal discordant results. It appears that the CX3CL1/CX3CR1 axis plays a direct role in neurodegeneration and/or neuroprotection depending upon the CNS insult. However, all the above studies focused on the role of CX3CL1/CX3CR1 signaling in pathological conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

21
536
4
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 561 publications
(583 citation statements)
references
References 43 publications
21
536
4
2
Order By: Relevance
“…These synapses are subsequently pruned and the neuronal circuits sculpted/refined by the appearance and proliferation of microglia during key critical periods (Brown & Neher, 2014; Kettenmann et al, 2013; Paolicelli et al, 2011). Evidence for the importance of microglia‐mediated synaptic pruning and refining during development comes from observations that transgenic mice with perturbed microglial function have impaired cognitive function and synaptic plasticity (Rogers et al, 2011), decreased synaptic pruning, and display autistic‐like phenotypes (Zhan et al, 2014). Microglia numbers are elevated during the period of synaptic pruning in development, and following this, microglia numbers then fall to those found in the adult mouse brain (Nikodemova et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…These synapses are subsequently pruned and the neuronal circuits sculpted/refined by the appearance and proliferation of microglia during key critical periods (Brown & Neher, 2014; Kettenmann et al, 2013; Paolicelli et al, 2011). Evidence for the importance of microglia‐mediated synaptic pruning and refining during development comes from observations that transgenic mice with perturbed microglial function have impaired cognitive function and synaptic plasticity (Rogers et al, 2011), decreased synaptic pruning, and display autistic‐like phenotypes (Zhan et al, 2014). Microglia numbers are elevated during the period of synaptic pruning in development, and following this, microglia numbers then fall to those found in the adult mouse brain (Nikodemova et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, fractalkine participates in the normal physiology of neuronal cells with a relevant role in neurodegenerative diseases and impaired recovery from sickness behavior (18). Furthermore, studies using animal models have described the effects of fractalkine on brain physiology, which are associated with depression and anxiety (6). Mice deficient in CX3CR1 cells have been shown to exhibit resistance to stress-induced depression-like behavior and to not respond to antidepressant treatment (19).…”
Section: Discussionmentioning
confidence: 99%
“…Fractalkine has also been involved in various non-immune mechanisms associated with psychiatric disorders, including inhibition of serotonergic neurotransmission by enhancement of GABA activity at serotonergic neurons, inhibition of glutamatergic activity in the hippocampal region, and regulation of processes of neuroplasticity, such as long term potentiation (6). These mechanisms are constantly affected in the manifestation of depression and anxiety, which are the most frequent comorbidities among CRC patients (7).…”
Section: Introductionmentioning
confidence: 99%
“…Although these developmental aspects appear to achieve resolution, adult CX3CR1-knockout mice still exhibit deficits indicative of malfunctioning circuitry. Rogers et al (2011) showed that these mice demonstrate impaired learning, probably accompanied by an inability to achieve long-term potentiation (LTP) in the hippocampus. The authors also showed that, compared with wildtype controls, the proinflammatory cytokine interleukin (IL)-1b in the CX3CR1-knockout mouse hippocampus is significantly increased.…”
mentioning
confidence: 99%